STRUKTUR LANSKAP PERENCANAAN PERKOTAAN DAN BUDAYA MELAYU DI JOHOR BAHRU, MALAYSIA: SEBUAH TINJAUAN [LANDSCAPE STRUCTURE OF URBAN PLANNING AND MALAY CULTURE IN JOHOR BAHRU, MALAYSIA: A REVIEW] - Fernandez, Donny; Syafri, Rifki Randa; Anaperta, Yoszi Mingsi; Nasti, Prayudi; Yulian, Yoga Ahmad; Delvina, Mery; Syah, Nurhasan; Heldi, Heldi (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
Landscape structure of green open spaces, urban forests, micro climate, comfort level, wildlife diversity, and malay culture are still under studied and the studies generally still focus on the aspect of urban planning. The quality of green open spaces and the comfort level of urban population will be better if the management of open spaces can be realized. This review article aims to measure the landscape structure and culture diversity and assess the correlation between the landscape structure and the comfort level of green open spaces in Johor Bahru, Malaysia. This observation review was carried out on several urban open space, urban forests, wildlife diversity sample unit and in depth interview. The result of this review article shows that on average, each the green open space in Johor Bahru has patch size of 6.78 hectares; the number of edges are 1962,04 meters; the edge density are 9,36 meters/hectare; the mean shape index are 2,75 and the mean patch fractal dimension are 1,41. The diversity of birds in Johor Bahru at whole green open space scales is low that is 0,28 in which the highest diversity index found in urban forests and yards is 0.37 while the lowest at 0.14 green line. From the eleven variables, there are five correlated variables which are mean patch size (X1), mean patch fractal dimension (X5), light intensity (Y3), the comfort index (Y4), and the percentage of canopy closure (Y5). The comfort index correlates the strongest than the rest of variables. Benefits of this research are to obtain information about the importance of determining the landscape structure of green open space that is appropriate to fix the comfort level and provide recommendations for policymakers and related institutions in developing the city.